In vitro Assessment of Coronal Discoloration from Endodontic Sealers - Makdad Chakmakchi; Chris Rahiotis; Nikolas P. Kerezoudis; Afrodite Kakaboura (University of Mosul, College of Dentistry, 2020)
Aims: to evaluate the effect of different endodontic sealers on the coronal discoloration of the tooth part. Materials and methods: Forty intact human upper incisors and canines free of caries, restorations and coronal discoloration were used in the study. Black rectangular pieces of adhesive tape, with a round opening of 3 mm in diameter was cut to match the size of colorimeter window, the tape was applied to the middle third of the buccul surface of the tooth to facilitate a means of enamel surface standardization for analysis and was further secured to the teeth crowns with cyanoacrylate glue. A colorimeter (Microcolor, Data Station, DeLange, Braive instruments, Leige, Belgium) according to the CIE-L*a*b* color system was used to evaluate the color of enamel in the coronal part before and after instrumentation and obturation of the teeth, employing a repeated measures design (n=5) per sample. Results: There was no statistically significant difference among the levels of time of different materials (p = 0.095). Sealapex was presented significant differences against control group. Conclusion: The selection of endodontic sealers should be based mainly on other criteria (setting time, microleakage and toxicity) and no on the potent ional staining.